Penerapan Konsep Geometri pada Siswa Sekolah Dasar Menggunakan Geoboard sebagai Alat Peraga Digital yang Interaktif - Viki Ardiansyah; Muhammad Farras Qoid Mufadhol; Kowiyah Kowiyah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Geoboard digital as an interactive educational tool to impart the principles of geometry in elementary school mathematics education. The primary objective of this study is to assess the efficacy of integrating geoboardDigital as an interactive learning medium for teaching geometry concepts in elementary school, while also evaluating the impact of its usage on students' comprehension and visualization skills in geometry. Additionally, it aims to compare the effectiveness of geoboardDigital with traditional methodologies in geometry education, as well as assess student response and engagement levels when utilizing geoboardDigital. Employing a qualitative descriptive approach, this research delves into how the integration of technology such as geoboardDigital enhances understanding and student engagement in geometry education. Data collection is carried out through observation, interviews, and field notes, with data triangulation methods utilized for analysis. The findings of this study demonstrate that the application of geoboardDigital effectively enhances students' visualization and comprehension of geometric concepts through its interactive functionalities. Interview results indicate that students find geoboardDigital to be easily accessible and engaging, particularly in creating geometric shapes using pins and virtual ribbons.